Banks in the Brazilian favela: A study of the relations between bank branches and residents of an urban region targeted by "pacification" policies - Lúcia Helena Alves Müller (economic sociology_the european electronic newsletter, 2018)
Despite their global reach, the processes leading to the financialization of social life are many and varied, both in terms of the agents responsible for their formulation and implementation and in relation to the dynamics and effects that they unleash in different national and local contexts. In Brazil, the government has played a key role in enabling and promoting these processes through the development of programs and initiatives in line with the proposals formulated by institutions like the World Bank and other organizations making up the international financial system. According to these agencies, increasing access to the financial system is one means of attaining higher levels of social inclusion, leading to an expansion of banking services and the supply of credit to low-income populations (Sen 2000; Kumar 2004; Banco Central do Brasil 2010)...
Keywords: 330